Computer-assisted survey interviewing of school-age children. - Rew L; Horner SD; Riesch L; Cauvin R (Advances in Nursing Science)
Longitudinal surveys of children in school settings can yield large volumes of data for use in exploring research questions that may influence development of intervention programs. However, traditional methods of data collection such as paper-and-pencil questionnaires or person-to-person interviewing present major threats to validity throughout the process of data collection, data management, and data analysis. The use of computer-assisted survey interviewing is an alternative that has both advantages and disadvantages. Lessons learned in the first wave of a longitudinal study of approximately 1161 children in fourth, fifth, and sixth grades illustrate both the strengths and limitations of this method.